From Awareness to Cultural Agency: EFL Colombian Student Teachers' Travelling Abroad Experiences - John Jairo Viafara González; J. Aleida Ariza Ariza (Universidad Nacional de Colombia, 2015)
Colombian English as a foreign language student teachers' opportunities to grow as educators through international sojourns do not usually subsume the traditional study and residence abroad goal. This was the case for our participants who engaged mainly in working abroad with study being ancillary. Fifty student teachers from two public universities reported how their international sojourn bolstered their intercultural learning. Three different programs, disconnected from participants' academic institutions, became vehicles for their experiences abroad. Surveys and interviews reveal that participants' origin, selected programs, and contextual circumstances influenced their intercultural learning. As a result, intercultural development gravitated towards awareness of intercultural patterns, critical reading of culture, and pre-service teachers' repositioning to build cultural agency. Implications suggest the need to connect traveling abroad programs to undergraduate curricula.